HIERARCHY AND RESPECT FOR ELDERS: REFLECTION OF FAMILY VALUES IN THE PAREMIOLOGICAL FUND OF THE RUSSIAN AND UZBEK LANGUAGES - Davlatmuratov Siroj Ravshanbekovich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  The  article  presents  a  comparative  linguocultural  analysis  of  the representation  of  the  concepts  of  "hierarchy"  and  "respect  for  elders"  in  the paremiological  fund  of  the  Russian  and  Uzbek  languages.  Based  on  proverbs  and sayings,  the  universal  features  and  ethnocultural  specificity  of  the  verbalization  of family values are examined. A corpus of 150 paremiological units (75 Russian and 75 Uzbek) was selected using continuous sampling. It has been established that the sacred-institutional character of hierarchy (based on the category of duty — farz) dominates in the Uzbek linguistic picture of the world, while in Russian paremiology the authority of  elders is based primarily  on  empirical  life experience  and pragmatic  irony.  The results  contribute  to  a  deeper  understanding  of  the  mechanisms  of  intercultural communication and the preservation of the national code.